SISTEM INFORMASI PENERIMAAN MAHASISWA BARU POLINDO INTERNASIONAL MENGGUNAKAN METODE PROTOTYPE - Kristanto, Titus; Putri Utoma, Anggraini; Rachmadhi Putra, Adzanil (Prosiding Seminar Nasional Teknologi dan Sistem Informasi, 2025)
The new student admissions process is a crucial part of the higher education administration system, requiring easily accessible, fast, and accurate information. Polindo Internasional, a vocational education institution, encounters numerous challenges in managing the manual registration process. This process leads to errors in recording, data processing, and the provision of unclear information to prospective students. The purpose of this research is to create a prototype method for designing and building a web-based information system for new student admissions. We carried out the development process iteratively and flexibly, receiving direct feedback from users, which led us to choose the prototype method. We conducted black box testing to ensure the system operates in accordance with the features specified. However, there are several limitations, including advanced security systems and unused automatic notification features. The results indicate that the developed system can handle all the requirements of the registration process, such as account registration, form filling, document upload, and payment administration verification.